Can lockdown and homeschooling change the outcome of urotherapy for lower urinary tract dysfunction in children?. Issue 5 (October 2021) - Akinci, Aykut; Baklaci, Can Utku; Oğuz, Efe Semetey; Kubilay, Eralp; Sanci, Adem; Aydoğ, Ezel; Hajiyev, Perviz; Soygür, Tarkan; Burgu, Berk
Summary: Objective: Lower urinary tract dysfunction (LUTD) are still important for both children and pediatric urologists. Urotherapy is recommended in LUTD treatment management. In our country, all citizens under the age of 20 were banned from going out of their homes due to Covid-19 and the homeschooling system has been adopted The aim of this study is to investigate the effect of lockdown and homeschooling on the effectiveness of urotherapy used for LUTD treatment. Methods: 83 patients were included in the study group. Besides 306 patients were determined as the control group (pre-Covid). The patients in the study group and the control group were compared in terms of improvement in Dysfunctional voiding and incontinence scoring system (DVISS), quality of life scores, bladder diary, Bristol stool scale, and treatment responses at 3rd and 6th months. Results: The study group and control group were compared in terms of DVISS, voiding frequency and incontinence in the voiding diary, quality of life score, and Bristol stool scale at admission visit and the group characteristics were similar. During the 6th month visit, the mean DVISS of the study group was found to be significantly lower (7.12 ± 3.48; 8.58 ± 4.06 respectively (p 0.002)). Daily voiding frequency was similar in the study group and the control group during the 2nd and 3rd visit. The study group's mean number of daily incontinence was significantly lower at visit 3 (0.57 ± 0.9; 0.94 ± 0.27, respectively (p 0.02).After six months of treatment, 13.3% of the study group patients had a complete response, 44.6% had a partial response, whereas 42.2% non-responders. In the control group, the response rates were as 5.9%, 39.2% and 54.9% respectively (p 0.02). Conclusions: LUTD is still very common in pediatric urology. Standard urotherapy is widely used in treatment management. According to our results, the success of standard urotherapy increases with lockdown and homeschooling. We have shown that the success of standard urotherapy can be improved by regulating environmental conditions. In terms of LUTD management, environmental conditions can be regulated to provide a better quality of life and a better cure in a more economical way. Summary Figure Evaluation of the study group and the control group in terms of Dysfunctional voiding and incontinence scoring system at visit times. Figure 1